Redesain Interior Sentra UKM MERR di Surabaya - Luh Ayu Ariesta Damayanti; Mariana Wibowo; Stephanie Melinda Frans (Intra, 2018)
Redesigning Interior of Sentra UKM MERR Surabaya is intended to help the various UKM in the "Sentra UKM MERR" in Surabaya improve their business. These UKM have only a few of visitors and are not been able to compete with similar store. The basic problem in this design is how interior design can fulfill UKM’s needs in Sentra UKM MERR and increase the product quality. To make it happen,  the designer using design thinking method with 10 stages including discovery, observe, empathize, stories to discover, frame and reframe, ideate, decide, prototype, validate, and iterate. The results of this design is Sentra UKM MERR interior design that can help improve the quality UKM product supported by maximizing the function of space that has not been fully utilized and visualized in the form of a presentation modeling and 3D rendering.